A comparative analysis of outcomes of root canal therapy for pediatric medicaid beneficiaries from New York State - Burns, Lorel E.; Gencerliler, Nihan; Terlizzi, Kelly; Wu, Yinxiang; Solis-Roman, Claudia; Gold, Heather T. (Frontiers in Oral Health, 2022)
Objectives: This study investigated differences in the provision of root canal therapy and outcomes in a publicly insured cohort of children and adolescents. Methods: New York State Medicaid administrative claims from 2006 to 2018 were analyzed. Enrollees aged 6-18 were included in the study if they had initial non-surgical root canal therapy (NSRCT), in the permanent dentition, that allowed for at least one year of post-treatment follow-up. Descriptive analyses, multivariable logistic regression, and multivariable Cox proportional hazard models were used to examine the association between demographic variables (gender, age, race/ethnicity, and area-based factors) and dental treatment provision and outcomes. Results: Male gender was associated with having more than one initial NSRCT (adjusted odds ratio (aOR) = 1.06; 95% Confidence Interval (CI) = 1.02-1.10), as was rurality (aOR = 1.15; 95% CI = 1.06-1.24). Black/African American (AA) and Hispanic children were less likely than non-Hispanic white children to have multiple NSRCTs (aOR = 0.88; 95% CI = 0.83-0.93 and aOR = 0.78; 95% CI = 0.74-0.83). Being older or female conferred a lower hazard of an untoward event (aHR = 0.93; 95% CI = 0.92-0.94 and aHR = 0.86; 95% CI = 0.81-0.91). Compared to non-Hispanic white children, Hispanic and Black/AA children had a higher risk of untoward event (aHR = 1.31; 95% CI = 1.21-1.41 and aHR = 1.55; 95% CI = 1.43-1.67) while children of Asian descent had a lower incidence after initial NSRCT (aHR = 0.79; 95% CI = 0.71-0.88). Conclusions: Race/ethnicity was the strongest demographic predictor of provision of initial non-surgical root canal therapy, subsequent placement of a permanent restoration and the occurrence of an untoward event after NSRCT in this cohort.